DAMPAK PENERAPAN E-SYSTEM PERPAJAKAN TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KANTOR PELAYANAN PAJAK (KPP) KANTOR WILAYAH JAKARTA SELATAN - Martini, Martini; Penawang, Stephanus Yoseph; Budi Purnomo, Taqwa Putra (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This research was conducted to determine the effect of the implementation of e-system (e-egistration, e-filling, e-SPT and e-billing) taxation on the level of compliance of individual taxpayers in paying taxes. The location of the study was conducted at the South Jakarta Regional Tax Office. This research is a quantitative study using primary data sources. The results showed that, the application of e-Registration and the application of e-Billing had a positive and significant effect on the level of compliance of individual taxpayers, while the application of e-Filling and application of e-SPT did not significantly influence the level of compliance of individual taxpayers. The level of tax compliance can be influenced by the application of e-system by 44.6%, the rest is influenced by other factors outside this study such as service quality, tax penalties and e-invoicing